Efficiency of Using Land Resources in The Agricultural Sector in The Context of Financial Instability - KOLOTUKHA Serge; GVOZDEJ Nataliia; CHVERTKO Liudmyla; KORNIIENKO Tetiana; VINNYTSKA Oksana; BOROVYK Petro (Communications of International Proceedings, 2021)
The article examines the areas of state support for the agricultural sector of Ukraine. The peculiarities of the system of state support of agricultural enterprises and measures to improve the mechanism of state support of domestic agricultural enterprises are considered. It is established that the state support of agricultural producers is an indispensable condition for sustainable development of the agricultural sector of the economy and ensuring food security of the state. The essence of land resources of the agricultural sector of the economy in conditions of financial instability is considered. The dynamics and structure of land resources of agricultural enterprises are studied. The peculiarities of the agricultural sector are also highlighted. Factors influencing the financial support of agricultural enterprises, the main suppliers of borrowed sources of financial resources for agricultural enterprises, internal factors of enterprise efficiency are identified. Possible sources of formation of own capital of agricultural enterprises are offered. As well as the most profitable sources of financial resources. We also considered the pros and cons of bank loans and the dynamics of their growth for all enterprises in Ukraine and leading countries.
Keywords: Agriculture; Agricultural Sector; Land Resources; State Regulation; Financing; Financial Instability.